2020
DOI: 10.3389/fspas.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Short Gamma-Ray Bursts From a Different Angle

Abstract: The recent coincident detection of gravitational waves (GW) from a binary neutron star merger with aLIGO/Virgo 1,2,3 and short-lived gamma-ray emission with Fermi/GBM 4,5 (called GW 170817) is a milestone for the establishment of multi-messenger astronomy. Merging neutron stars (NS) represent the standard scenario for short-duration (< 2 sec) gamma-ray bursts 6 (GRBs) which are produced in a collimated, relativistically expanding jet with an opening angle of a few degrees and a bulk Lorentz factor of 300-1000.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…We conclude that the overall properties of GRB150101B are naturally accounted for by a structured jet viewed off-axis. This implies that in the nearby (z<0.2) Universe, where off-axis explosions are detectable by current gamma-ray facilities 54 , the true-to-observed ratio of short GRBs is much smaller than the beaming correction factor (∼300) of the uniform jet model 51,55 . Based on our model of a Gaussian jet, we show in Figure 7 some predictions for X-ray searches of GW counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the overall properties of GRB150101B are naturally accounted for by a structured jet viewed off-axis. This implies that in the nearby (z<0.2) Universe, where off-axis explosions are detectable by current gamma-ray facilities 54 , the true-to-observed ratio of short GRBs is much smaller than the beaming correction factor (∼300) of the uniform jet model 51,55 . Based on our model of a Gaussian jet, we show in Figure 7 some predictions for X-ray searches of GW counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a group of similar GRBs and suggested that a good fraction of the previously detected faint short GRBs is not at large redshifts, but local, at redshift smaller than 0.1, seen off-axis (Fig. 36, [23]). We incorporated off-axis emission in the estimate of the rates of short GRBs and predicted that the majority of future GW-detections of NS-NS mergers will be accompanied by faint γ-ray emission [23], contrary to previous thinking and still open for an observational test.…”
Section: Glast/fermimentioning
confidence: 71%
“…36, [23]). We incorporated off-axis emission in the estimate of the rates of short GRBs and predicted that the majority of future GW-detections of NS-NS mergers will be accompanied by faint γ-ray emission [23], contrary to previous thinking and still open for an observational test. Overall, this event was a confirmation of MPE's previous successful scientific strategy, as the only two gamma-ray measurements were taken with detectors built under MPE leadership (on INTEGRAL-SPI/ACS and Fermi/GBM), and additionally important kilonova observations could be provided with MPE's GROND imager [144].…”
Section: Glast/fermimentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution also hints that a small fraction of Fermi bursts may contain nearby events viewed at large angles. There have been claims of such local events from archival Fermi and Swift data (Burgess et al 2017;Troja et al 2018;von Kienlin et al 2019).…”
Section: Detected Populationmentioning
confidence: 99%